CONTRIBUTION OF WORKING CAPITAL MANAGEMENT AND LEVERAGE TO INCREASING VALUE OF MANUFACTURING COMPANIES AND CONJUNTURE EFFECT FROM PROFITABILITY RATIO MODEL: AN REALITY CASE STUDY IN INDONESIA STOCK EXCHANGE - Jerni Duma Sari Rambe; Nova Sari Manullang; Daniel Ortega Tambunan; Mangasi Sinurat; Maulana Majied Sumatrani Saragih (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The company is a group of people who are members of an organization who work to achieve certain goals. One of the most basic company goals is to obtain maximum profit or profit from the business activities carried out by the company. The purpose of establishing a company is not only to achieve maximum profit, but also aims to increase the prosperity of parties related to the company's business activities, such as shareholders and stakeholders so that the value of the company increases.The research method used is quantitative data method. Working Capital Management has a positive and significant effect on Firm Value, Leverage has no significant effect on Firm Value, Working Capital Management and Leverage have no simultaneous significant effect on Firm Value. Company value can be used as the basis for making investment decisions because this aspect measures the ability of the company's assets to generate a return on investment made in the company's asset instruments.